2013
DOI: 10.1007/s10652-013-9286-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient numerical computation and experimental study of temporally long equilibrium scour development around abutment

Abstract: For the abutment bed scour to reach its equilibrium state, a long flow time is needed. Hence, the employment of usual strategy of simulating such scouring event using the 3D numerical model is very time consuming and less practical. In order to develop an applicable model to consider temporally long abutment scouring process, this study modifies the common approach of 2D shallow water equations (SWEs) model to account for the sediment transport and turbulence, and provides a realistic approach to simulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…It was observed that d se around the pier always occurred at the upstream pier nose and the scour hole geometry was similar at the left and right sides of the pier. Similar findings have also been found by many researchers [2,[27][28][29].…”
Section: Present Experimental Worksupporting
confidence: 92%
“…It was observed that d se around the pier always occurred at the upstream pier nose and the scour hole geometry was similar at the left and right sides of the pier. Similar findings have also been found by many researchers [2,[27][28][29].…”
Section: Present Experimental Worksupporting
confidence: 92%
“…The analytical calculation of the turbulent dam break wave gives efficient solutions with the presences of bed friction as compared to numerical model, i.e. as presented in Pu et al 6,14 . This study also adopts the conceptual model of Whitham 12 in which the ideal fluid flow is used behind the frictionally dominated wave front region.…”
Section: Turbulent Results and Discussionmentioning
confidence: 99%
“…for flood flow. In terms of modelling sedimentation within flood inundation, various studies have proposed time-effective models to represent the transport phenomenon accompanied in turbulence flow and flooding [1,4,10] and further study at Pu and Lim [5] suggested an effective sediment transport modelling system to simulate turbulent flow sedimentation, e.g. in concentrated sediment flashing and in fast scouring flow, suitable to be deployed in flashflood modelling.…”
Section: Modelling Methodology Of Nfmmentioning
confidence: 99%